A collaborative experimentation environment for biosciences. (14th October 2004) - Kaletas, E.C.; Afsarmanesh, H.; Hertzberger, L.O.
Challenges in biosciences include among others, description and management of the information related to experiments, which utilise advanced technologies for the storage, manipulation, and integration of data that they produce, and high-performance computers and highly heterogeneous, geographically dispersed information sources for the analysis of their results. In this paper, we propose and describe a "collaborative experimentation environment". We describe how enabling technologies and paradigms such as Grid, federated information management, virtual laboratories, and virtual organisations can be applied for developing such an environment. The DNA micro-array application case and the domain of biosciences are chosen to exemplify the proposed mechanisms and system.